Challenges in semiconductor - He, Xiaoxiao (Nanyang Technological University, 2020)
With rapid development of society, the world trends to be digital. Digital products has been an indispensable part for work, study, and daily life. Communication over handphones and computers in workplace and schools, even at home is common for most the people nowadays. Those electronic devices and internet cannot be constructed without memory devices. A memory device provides information and storage in digital systems. Therefore, semiconductor industry chips boom followed the trend up of digital systems. Semiconductor industry which manufacture memory chips also become one of the most significant industry in the world. During past decades, more and more semiconductor manufacturing companies were established. Manufacturers start to invest in innovation of technology as solution to improve product quality and reduce cost and cycle time etc. In order to bring up their competitiveness, automation is one of the innovation categories.This project aims to design an automation system in term of process operation. Automation is technology that uses robot to do the jobs instead of manpower. It effectively helps in high volume and repeatable tasks. In dry etch module of a semiconductor manufacturing fab, germ hold operation is one of the most important operations which is used to perform process control. Germ hold is repeated in daily work, it is time consuming and it takes up high percentage of workload. This project will design a system with Robotic Process Automation tool to automate germ operation. The system is expected to perform operation automatically to save manpower and reduce cycle time and cost, as well as reducing operation errors.